Smartphone‐based Electrochemical On‐site Quantitative Detection Device for Nonenzyme Lactate Detection. Issue 9 (13th April 2022) - Zhang, Xiaotao; Wei, Yi; Wu, Huihuang; Yan, Hongli; Liu, Yiming; Lučev Vasić, Željka; Pan, Haibo; Cifrek, Mario; Du, Min; Gao, Yueming
Abstract: On‐site quantitative detection provides the opportunity for accurate and timely health care, clinical diagnosis, environmental monitoring, and food analysis. A variety of portable electrochemical detection instruments have been developed at present for on‐site quantitative detection use, including commercially available portable potentiostats, but the reality is that these electrochemical detection devices still have the problem of narrow output voltage range and detection current range, and their performance of output voltage resolution and detection current resolution is still unsatisfactory. The narrow voltage or current range makes it difficult for some chemical reactions with peaks outside the range to proceed, and the insufficiency of voltage resolution and detection current resolution are key parameters restricting the detection accuracy of existing devices. In this regard, it is urgent to carry out partial transformation of the existing device to increase the use range and detection accuracy of the device. In the current work, a smartphone‐based electrochemical on‐site quantitative detection device was developed. The device comprises a portable small potentiostat, a smartphone equipped with a specially designed Android electrochemical detection application, and a disposable sensor (NiONP modified screen‐printed electrode [SPE]). The potentiostat can realize electrochemical detection methods, including cyclic voltammetry, chronoamperometry, and differential pulse voltammetry. In addition, the potentiostat can output a potential range −2.047∼+2.047 V with a current detection sensitivity scale 1×10 −8 ∼1×10 −3  A, and the current detection range could reach ±10 nA∼±10 mA. Most importantly, the current detection resolution of the potentiostat can reach 0.003 % (3.125 pA on ±10 nA range). The smartphone was used for communicating with the potentiostat, setting detection parameters, and mapping voltammograms in real time. The SPE was modified with nickel oxide nanoparticles and perfluorinated resin solution, which were employed as sensors to convert and amplify the electrochemical current response during the on‐site quantitative detection. Results indicated that the device features excellent performance for the lactate detection. The device covered a linear range 0.1∼30 mM on lactate detection with the correlation coefficient (R 2 ) reaching 0.997. Abstract :